Early, rapidly progressive enteral nutrition promotes growth of very low birth weight (VLBW) infants. (19th May 2017) - Flidel-Rimon, Orna; Raz, Moriya; Balla, Uri; Hofi, Lilach; Juster-Reicher, Ada; Shinwell, Eric S.
Abstract: Aim : This study describes the effects of a quality improvement program to promote improved postnatal nutrition on the growth of very low birth weight (VLBW) infants. Methods : Daily data regarding nutrition and growth were collected from the medical record of VLBW infants born during 1995–2010. The infants were grouped by year of birth in order to compare infants from before, during and after the policy change. Evaluation of growth included age in days at a return to birth weight and the proportion of infants with weight below the 10th percentile at discharge. Results : The caloric and protein intake improved significantly. The age at a return to birth weight fell ( p < 0.01) from 14.6 ± 5 d to 11 ± 8 d after the change. The proportion of infants with a discharge weight below the 10th percentile for corrected age fell ( p < 0.01) from 72.1% to 42.1%. Data on enteral feeding showed that increased rate of enteral feeds (EF) was associated with better growth ( p < 0.001). Conclusion : Increasing awareness led to increase in caloric and protein intake in VLBW infants. Aggressive EF was associated with more rapid weight gain. However, the provision of protein and calories during the first 2 weeks of life still falls short of the latest European Society of Pediatric Gastroenterology, Hepatology and Nutrition recommendations.